Sistema de acasalamento e evolução do cuidado paternal em duas espécies de opiliões da subfamília Heteropachylinae (Opiliones : Gonyleptidae) - Gonçalves, Taís Maria de Nazareth (2008)
Females of the harvestmen Chavesincola inexpectabilis and Pseudopucrolia sp. lay eggs inside natural cavities in ravines. These cavities are monopolized by some males, which fight against conspecific males, allowing the access only of ovigerous females. The reproductive success of males is directly associated to the ownership of a nest and the mating system of both species may be characterized as resource defense polygyny . Laboratory observations with Pseudopucrolia indicate that male size is not a sexually selected trait. On the other hand, male behavioral features seem to be related to the probability of achieving copulations: the greater the nest tenure and the permanence of a given male inside a nest, the higher his chances of mating. Additionally, results obtained with Pseudopucrolia sp. provide support to some of the main predictions of the theory of evolution of paternal care in arthropods via sexual selection: (1) females are iteroparous; (2) guarding males have many mating opportunities; (3) paternal care creates more opportunities for females to forage; (4) females prefer to copulate with guarding males; and (5) males are willing to guard unrelated eggs. Mapping the forms of parental investment in the phylogeny of the Gonyleptidae, it is possible to infer that paternal care has evolved at least three times within the family: once in the Heteropachylinae, at least once in the Gonyleptinae, and once at the base of the clade Progonyleptoidellinae + Caelopyginae.